What drives health-care spending in China? A nationwide decomposition analysis. Issue 9 (19th February 2023) - Li, Keyang; Qin, Yu; Wei, Guoxu; Wu, Jing
ABSTRACT: In this study, we explore the geographic variation in health-care spending and its driving factors in China, using a nationwide and claim-level sample of inpatients ensured under the urban basic medical insurance schemes in 2010. We show geographic variation in health-care spending is substantial in China and is significantly larger than Medicare spending in the US. The substantial geographic variation is primarily driven by the quantity variation. We also discuss the potential correlates of the quantity of health care at the city level. The findings imply possible allocation inefficiency in China's current urban health-care system.